2007
DOI: 10.1097/01.wnf.0000240940.13876.17
|View full text |Cite
|
Sign up to set email alerts
|

The Deployment of Intersensory Selective Attention

Abstract: : This increase of attention-related anticipatory alpha over the right parieto-occipital scalp suggests that theanine may have a specific effect on the brain's attention circuitry. We conclude that theanine has clear psychoactive properties, and that it represents a potentially interesting, naturally occurring compound for further study, as it relates to the brain's attentional system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Post-hoc tests revealed that this main effect was driven by higher posterior alpha power in the Auditory condition as compared to the Visual and Audio-Visual conditions (Tukey HSD, both p < .01, d = .55 and .67 respectively). As previous experiments had implicated alpha activity in selective ignoring of task-irrelevant information (Foxe, Simpson, & Ahlfors, 1998; Gomez-Ramirez et al, 2007; Mathewson et al, 2009; Snyder & Foxe, 2010; Payne & Sekuler, 2014), the continuous posterior alpha activity seen during Auditory trials is likely a marker of the suppression of visual input, perhaps so as to advantage auditory input.…”
Section: Resultsmentioning
confidence: 89%
“…Post-hoc tests revealed that this main effect was driven by higher posterior alpha power in the Auditory condition as compared to the Visual and Audio-Visual conditions (Tukey HSD, both p < .01, d = .55 and .67 respectively). As previous experiments had implicated alpha activity in selective ignoring of task-irrelevant information (Foxe, Simpson, & Ahlfors, 1998; Gomez-Ramirez et al, 2007; Mathewson et al, 2009; Snyder & Foxe, 2010; Payne & Sekuler, 2014), the continuous posterior alpha activity seen during Auditory trials is likely a marker of the suppression of visual input, perhaps so as to advantage auditory input.…”
Section: Resultsmentioning
confidence: 89%
“…Gomez-Ramirez et al (2007) measured electroencephalographic (EEG) response during rest and after 250 mg of L-theanine, and found L-theanine related increased anticipatory alpha band activity over parietal and occipital scalp regions, suggesting reduced arousal states and potentially enhanced effortful control of attention.…”
Section: L-theanine and Attentional Controlmentioning
confidence: 99%
“…This study aimed to expand on prior research in selective attention which had shown that alpha-band power increases index the degree of attentional suppression in visuospatial attention tasks (Worden et al, 2000; Sauseng et al, 2005; Yamagishi et al, 2005; Kelly et al, 2006, 2009, 2010; Thut et al, 2006; Rihs et al, 2007; Gomez-Ramirez et al, 2009), intersensory attention tasks (Foxe et al, 1998; Fu et al, 2001; Gomez-Ramirez, et al, 2007), sustained visual attention tasks (Dockree et al, 2007; O’Connell et al, 2009) and audiospatial attention tasks (Kerlin et al, 2010; Banerjee et al, in press). We asked if alpha-band mediated suppression would be observed in a feature-based selective attention task.…”
Section: Introductionmentioning
confidence: 97%